Value-based oral health care: moving forward with dental patient-reported outcomes - Listl, Stefan (The journal of evidence based dental practice, 2019)
Value-based oral health care is about improving people's oral health outcomes divided by the costs involved. This article addresses five questions (the “5 W's”) pertaining to the measurement of oral health outcomes: why oral health outcomes should be measured, what should be measured, by whom, when, and where. Therefore, dental patient-reported outcome measures offer great potential for driving improvements in oral health care. For illustration, a tentative set of seven key relevant items is presented, which comprises the four dimensions of oral health-related quality of life and the three dental conditions with the highest burden of disease. Through promoting the ample use of oral health outcome measures, it is hoped that this article can contribute to expedite value-based oral health care.
Gesehen am 06.02.2020